2012
DOI: 10.1016/j.ypmed.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

n−3 fatty acids prevent impairment of neurogenesis and synaptic plasticity in B-cell activating factor (BAFF) transgenic mice

Abstract: Objective. Autoimmune-prone B-cell activating factor transgenic mice, a mouse model of systemic lupus erythematosus and Sjögren's syndrome exhibit neuroinflammation, anxiety-like phenotype, deficit in adult hippocampal neurogenesis and impaired neurogenesis-dependent and neurogenesis-independent dentate gyrus long-term potentiation. Given that n−3 polyunsaturated fatty acids regulate hippocampal plasticity and inflammatory responses, we investigated whether n−3 polyunsaturated fatty acids-enriched diet might p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…However, our results obtained by qRT-PCR indicate that synaptic plasticity may be increased at pubertal age in the cortex, while it remains unaffected at adult age. Several studies demonstrated an increased expression of presynaptic and postsynaptic proteins after n-3 PUFA supplementation, hinting at increased synaptogenesis either early on in life or during aging [22,51,86]. Our data on synaptophysin expression led us to hypothesize that synaptogenesis is stimulated at adolescent age on an n-3 PUFA adequate diet and reaches a plateau before adult age.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…However, our results obtained by qRT-PCR indicate that synaptic plasticity may be increased at pubertal age in the cortex, while it remains unaffected at adult age. Several studies demonstrated an increased expression of presynaptic and postsynaptic proteins after n-3 PUFA supplementation, hinting at increased synaptogenesis either early on in life or during aging [22,51,86]. Our data on synaptophysin expression led us to hypothesize that synaptogenesis is stimulated at adolescent age on an n-3 PUFA adequate diet and reaches a plateau before adult age.…”
Section: Discussionsupporting
confidence: 51%
“…Besides, the expression of inflammatory markers remained unaffected by n-3 PUFA availability during development. N-3 PUFA supplementation has been shown to decrease neuroinflammation in immune deprived and aged mice [86,88]. It is not likely that the young, healthy C57BL/6J mice used in our experiments are prone to inflammation at this stage in life, which is supported by the fact that n-3 PUFA availability did not affect inflammatory markers.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…For instance, dietary supplementation with n-3 PUFAs restored neurogenic markers in the DG of a mouse model of systemic lupus erythematosus and Sjögren's syndrome, characterised by lower levels of AHN among other biological deficits [181]. Perinatal supplementation with n-3 PUFA also mitigated the impairment in working and short-term memory and altered fear response observed in rats as a consequence of sevoflurane-induced neurotoxicity, likely through decreased apoptosis and enhancement of hippocampal cell proliferation [182].…”
Section: Dietary Content: Focus On N-3 Fatty Acids As Potent Food-mentioning
confidence: 99%